2012
DOI: 10.1111/j.1600-0714.2012.01184.x
|View full text |Cite
|
Sign up to set email alerts
|

Oral and Genital Human Herpesvirus 8 and Human Papillomavirus in heterosexual partners

Abstract: Based upon the results of this study, co-infection between HPV and HHV-8 in malignant and pre-malignant penile lesions is an unlikely finding.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 38 publications
(56 reference statements)
0
7
0
Order By: Relevance
“…In comparison, the latest research showed that 18/31 (58 percent) of female genital brush studies have identified HPV DNA, whereas none of those female brushstrokes is positively KSHV DNA [14]. Another study found that there was no detectable KSHV DNA in the cervical secretion of 112 females, although 2.7% and 24% respectively of serum samples from the same group were found to contain latent and lytic KSHV antibodies [15].It's now almost unclear whether HPV oncogenic gene expression in cervical cancer cells is regulated by KSHV infection or by KSHV-encoded proteins.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…In comparison, the latest research showed that 18/31 (58 percent) of female genital brush studies have identified HPV DNA, whereas none of those female brushstrokes is positively KSHV DNA [14]. Another study found that there was no detectable KSHV DNA in the cervical secretion of 112 females, although 2.7% and 24% respectively of serum samples from the same group were found to contain latent and lytic KSHV antibodies [15].It's now almost unclear whether HPV oncogenic gene expression in cervical cancer cells is regulated by KSHV infection or by KSHV-encoded proteins.…”
Section: Discussionmentioning
confidence: 93%
“…Another study found that there was no detectable KSHV DNA in the cervical secretion of 112 females, although 2.7% and 24% respectively of serum samples from the same group were found to contain latent and lytic KSHV antibodies [15].It's now almost unclear whether HPV oncogenic gene expression in cervical cancer cells is regulated by KSHV infection or by KSHV-encoded proteins. [12][13][14][15][16].The major viral oncoproteins closely related to cervical human carcinogenesis are high-risk HPV, as encoded E6 and E7 proteins, for example, under the subtypes 16 and 18 [1,2]. Proteins E6 and E7 can bind to the family proteins P53 and Rb resulting in the control and conversion of the cell cycle [3], respectively.E6 and E7 proteins have been recently shown to be interacting, regulating or contributing to the oncogenesis, and many more cellular elements, including proteins that control cell epigenetic traces and splicing modifications [1,3].…”
Section: Discussionmentioning
confidence: 99%
“…HHV-8 infection was found in 16% and 8% of Spanish sex workers and general population, respectively and the odds ratio was found to be 2.2 [ 24 ]. HHV-8 DNA was also found in 3.2% and 0% of male and female genital brushing in Brazil, respectively [ 25 ]. However, HHV-8 DNA was not detected in any normal cervical secretions of Swedish women samples [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…6 Another study reported the presence of HPV in 54% of women with clinically healthy oral mucosa but whose sexual partners presented HPV-associated genital lesions. 14…”
Section: Discussionmentioning
confidence: 99%
“…6,20 Several studies have linked multiple partners for oral sex and kissing with increased risk for acquisition of HPV. 3,7,14 Inconsistent use of preservatives can be a prevalent risk factor among sexually active young adults in Brazil. Barbosa and Koyama 21 described the Brazilian North and Northeast regions with the highest reports of men with more than one sexual partner/year.…”
Section: Non-usersmentioning
confidence: 99%